A study on coronary bifurcation lesions and procedural outcome at Manmohan cardiothoracic vascular and transplant center, Kathmandu, Nepal - Poudel, Chandra Mani; Shakya, Smriti; Gajurel, Ratna Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Manandhar, Bhawani; Khanal, Rajaram (Nepalese Heart Journal, 2022)
Background and Aims: Coronary bifurcation lesions are associated with high atherosclerotic plaque burden due to turbulent blood flow and high shear stress. There are various strategies for bifurcation stenting however, they are often prone to major cardiac events during percutaneous coronary intervention. The aim of this study was to assess the clinical profile and procedural outcome of patients with coronary bifurcation lesions. Methods: This retrospective study was carried out at Manmohan Cardiothoracic Vascular and Transplant center, Kathmandu, Nepal. Two hundred and eight patients were enrolled in this study who had coronary bifurcation lesions seen on invasive coronary angiography from August 2017 to October 2021. The procedural complications were assessed. Results: The mean age of patients with coronary bifurcation lesions was 61.48±11.19 years. Out of total 208 patients, 77% were males. True bifurcation lesion was seen in 65.4% of patients. Left anterior descending artery with diagonal was the most common bifurcation lesion (67.3%). The provisional stenting was done in 80.8% of patients and rest underwent 2-stent strategy. The complications mainly observed during the provisional stenting were plaque shift and side branch dissection. Conclusion: The provisional stenting is the most preferred and suitable technique for most bifurcation lesions if technically feasible.